2014
DOI: 10.1371/journal.pone.0095676
|View full text |Cite
|
Sign up to set email alerts
|

Function of Chemokine (CXC Motif) Ligand 12 in Periodontal Ligament Fibroblasts

Abstract: The periodontal ligament (PDL) is one of the connective tissues located between the tooth and bone. It is characterized by rapid turnover. Periodontal ligament fibroblasts (PDLFs) play major roles in the rapid turnover of the PDL. Microarray analysis of human PDLFs (HPDLFs) and human dermal fibroblasts (HDFs) demonstrated markedly high expression of chemokine (CXC motif) ligand 12 (CXCL12) in the HPDLFs. CXCL12 plays an important role in the migration of mesenchymal stem cells (MSCs). The function of CXCL12 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, SDF-1α, a protein produced via alternative splicing of the SDF-1 gene, was highly expressed in human PDL fibroblasts. Indeed, the expression level was much higher than that in human dermal fibroblasts (17). Hasegawa et al reported that SDF-1α expression was increased in hPDLF by treatment with transforming growth factor-β1 but inhibited by treatment with basic fibroblast growth factor-2 (18), which suggests that fibroblasts exhibit cell type-specific reactivity to external stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, SDF-1α, a protein produced via alternative splicing of the SDF-1 gene, was highly expressed in human PDL fibroblasts. Indeed, the expression level was much higher than that in human dermal fibroblasts (17). Hasegawa et al reported that SDF-1α expression was increased in hPDLF by treatment with transforming growth factor-β1 but inhibited by treatment with basic fibroblast growth factor-2 (18), which suggests that fibroblasts exhibit cell type-specific reactivity to external stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…Stromal cell‐derived factor 1 is believed to have important roles in recruiting stem/progenitor cells, such as MSCs, to injury sites during tissue repair/regeneration. Periodontal ligament fibroblasts are known to secrete SDF‐1 and the SDF‐1 may induce migration of MSCs to the periodontal ligament in order to maintain rapid turnover of the periodontal ligament . It has been shown that BMP‐9 enhances secretion of SDF‐1 by human bone marrow stem cells .…”
mentioning
confidence: 99%
“…In the present study, we demonstrated that PDL cells synthesize high levels of SDF‐1 and that this synthesis was further increased after tooth replantation in vivo . Similarly, a recent study reported that PDL‐derived cells express SDF‐1 at higher levels than do dermal fibroblasts . These results indicate that high SDF‐1 expression in the PDL may contribute to the migration of BM‐derived stem cells, resulting in the rapid turnover rate of the PDL.…”
Section: Discussionmentioning
confidence: 60%
“…A recent study reported that PDL‐derived cells express SDF‐1 at high levels ; therefore, we analyzed the concentration of SDF‐1 in PDL cell‐conditioned medium (PDL‐CM). The concentration of SDF‐1 in PDL‐CM was significantly higher than that in control culture medium and osteoblast‐CM (Fig.…”
Section: Resultsmentioning
confidence: 99%